2012 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology 2012
DOI: 10.1109/wi-iat.2012.115
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Turkish Political News

Abstract: In this paper, sentiment classification techniques are incorporated into the domain of political news from columns in different Turkish news sites. We compared four supervised machine learning algorithms of Naïve Bayes, Maximum Entropy, SVM and the character based N-Gram Language Model for sentiment classification of Turkish political columns. We also discussed in detail the problem of sentiment classification in the political news domain. We observe from empirical findings that the Maximum Entropy and N-Gram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 11 publications
(6 reference statements)
0
71
0
5
Order By: Relevance
“…Kaya et al (2012) investigated the performances of supervised machine learning algorithms of Naive Bayes, maximum entropy, SVM and the character based n-gram language models. It was observed that maximum entropy and the n-gram outperformed the SVM and Naive Bayes and achieved 76-77% accuracy with different features.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaya et al (2012) investigated the performances of supervised machine learning algorithms of Naive Bayes, maximum entropy, SVM and the character based n-gram language models. It was observed that maximum entropy and the n-gram outperformed the SVM and Naive Bayes and achieved 76-77% accuracy with different features.…”
Section: Related Workmentioning
confidence: 99%
“…It was observed that maximum entropy and the n-gram outperformed the SVM and Naive Bayes and achieved 76-77% accuracy with different features. Subsequently, Kaya (2013) described an improved version of their previous system by implementing transfer learning into the existing framework. This system accomplished more than a 25% improvement over the previous system and with all of the three machine learning approaches (Naive Bayes, SVM and maximum entropy), accuracy values over 90% were obtained for the sentiment classification of Turkish political columns.…”
Section: Related Workmentioning
confidence: 99%
“…gibi mesaj içeriğinde gözlenen nitelikler kullanılmaktadır [21], [25], [26]. Ayrıca, ön tanımlı sözlükler ve semantik işlemlere ihtiyaç duyulan doğrusal sınıflandırıcılar etiketleme amacıyla kullanılmaktadır [27], [28]. Bu yöntemlerle duygu analizinde elde edilen başarı oranının ise %59-87 arasında olduğu görülmektedir [30].…”
Section: Duygu Sınıflandırmasıunclassified
“…Literatürde duygu analizi alanındaİngilizce için birçok istatistiksel ve dilbilimsel çalışma yapılmış olmakla beraber [6][7][8][9] Türkçe için henüz çok fazla çalışma yayınlanmamıştır [5], [14]. Bu bildiride öncelikli olarak Twitter üzerinden çekilen Türkçe bir veri seti oluşturulmuştur.…”
Section: Introductionunclassified